The Diffusion of New Institutions: Evidence from Renaissance Venice's Patent System - Stefano Comino; Alberto Galasso; Clara Graziano (Center for Economic Studies and ifo Institute (CESifo), 2017)
What factors affect the diffusion of new economic institutions? This paper examines this question exploiting the introduction of the first regularized patent system which appeared in the Venetian Republic in 1474. We begin by developing a model which links patenting activity of craft guilds with provisions in their statutes. The model predicts that guild statutes that are more effective at preventing outsider's entry and at mitigating price competition lead to less patenting. We test this prediction on a new dataset which combines detailed information on craft guilds and patents in the Venetian Republic during the Renaissance. We find a negative association between patenting activity and guild statutory norms which strongly restrict entry and price competition. We show that guilds which originated from medieval religious confraternities were more likely to regulate entry and competition, and that the effect on patenting is robust to instrumenting guild statutes with their quasi-exogenous religious origin. We also find that patenting was more widespread among guilds geographically distant from Venice, and among guilds in cities with lower political connection which we measure exploiting a new database on noble families and their marriages with members of the great council. Our analysis suggests that local economic and political conditions may have a substantial impact on the diffusion of new economic institutions.
Keywords: O33; O34; K23; 330; patents; competition; guilds; institutions